Обобщение теоремы Н.Огата об абсолютной сходимости коэффициентов лакунарных рядов - Шульгина-Таращук, А.С.; Толеуханова, Р.Ж. (Изд-во КарГУ, 2010)
Зерттеулердің қуатты əдiсі болып периодты функцияларды лакунарлық қатарлар арқылы беруге негiзделген гармониялық талдау табылады. Мақалада О.Састың теоремасы шығатын ең жақсы жуықтаулардың терминдерiндегi тригонометриялық жүйе бойынша лакунарлық қатарлардың жинақтылығының жеткiлiктi шарты алынған. Шарттың жағдайында Я.Р.Патадиа, В.М.Шах жəне Н.Огаталардың теоремалары қарастырылған. In the article the sufficient condition of convergence lacunar numbers on trigonometrical system in terms of the best approaches from which O.Sasa's theorem follows is received, and in case of a condition J.R.Patadia, V.M.Shaha and N.Ogata's theorems turn out. The decomposition method abreast is an effective method of studying of functions, calculation and estimations of integrals, the decision of the every possible equations (algebraic, differential, integrated). A powerful method of research is the harmonious analysis based on representation of periodic functions lacunar by numbers.
The generalization of theorem N.Ogata about absolute convergence of factors lacunars of numbers